PELATIHAN PEMBUATAN DAN PENGGUNAAN MEDIA TANAM SEMI HIDROPONIK PADA PETANI DESA RAHONG - Holilah, Holilah; Maelani, Puspita; Habibie Sukarna, Royan; Januriana, Andi Moch; Hilman, Mohamad; Solihin, Solihin (Gapenas Publisher, 2025)
This training aims to increase the knowledge and skills of Rahong Village farmers in utilizing semi-hydroponic technology as an alternative planting medium that is effective, efficient and environmentally friendly. The semi-hydroponic method offers a practical solution to overcome the limitations of conventional agricultural land and increase plant productivity. This activity includes two main stages, namely making hydroponic planting media which involves the use of local and cheap materials, as well as guidelines for the use and maintenance of hydroponic systems for various types of plants. Through a participatory approach, training is carried out by delivering theoretical material, direct demonstrations and practice by participants. The results of the training and use of semi-hydroponic planting media show a significant increase in farmers' understanding and ability to implement semi-hydroponics. Participants are able to design a simple semi-hydroponic system and understand the steps for maintaining plants. It is hoped that this training will encourage the widespread adoption of semi-hydroponic technology in Rahong Village to improve the quality and quantity of agricultural products, support sustainable agriculture, support food security, and improve the welfare of local communities. This training aims to increase the knowledge and skills of Rahong Village farmers in utilizing semi-hydroponic technology as an alternative planting medium that is effective, efficient and environmentally friendly. The semi-hydroponic method offers a practical solution to overcome the limitations of conventional agricultural land and increase plant productivity. This activity includes two main stages, namely making hydroponic planting media which involves the use of local and cheap materials, as well as guidelines for the use and maintenance of hydroponic systems for various types of plants. Through a participatory approach, training is carried out by delivering theoretical material, direct demonstrations and practice by participants. The results of the training and use of semi-hydroponic planting media show a significant increase in farmers' understanding and ability to implement semi-hydroponics. Participants are able to design a simple semi-hydroponic system and understand the steps for maintaining plants. It is hoped that this training will encourage the widespread adoption of semi-hydroponic technology in Rahong Village to improve the quality and quantity of agricultural products, support sustainable agriculture, support food security, and improve the welfare of local communities.